1999
DOI: 10.1021/es980717a
|View full text |Cite
|
Sign up to set email alerts
|

Aeration Effects on the Partitioning of a PCB to Anoxic Estuarine Sediment Pore Water Dissolved Organic Matter

Abstract: Pore water dissolved organic matter (DOM) plays an important role in the distribution, mobility, and bioavailability of hydrophobic organic chemicals (HOCs) in sediment environments. The effect of aeration on the partitioning of 2,2′,4,4′-tetrachlorobiphenyl (TeCB) to anoxic pore water DOM from three estuarine sites was investigated. Pore water DOM was fractionated into molecular size and polarity fractions by ultrafiltration and XAD-8 resin chromatography. Total organic carbon analysis was utilized to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 51 publications
(93 reference statements)
1
27
0
Order By: Relevance
“…This was explained by coprecipitation of interstitial colloids and DOM and associated POPs when ferrous oxides precipitated following aeration. Pedersen et al (16) report a 24% decrease in pore water DOM when aerating estuarine sediments, attributable to DOM coagulation with precipitating Fe(OH)3. Baltic Sea sediments contain large amounts of organic matter and coprecipitation effects are plausible explanations to the stabilized or reduced contaminant fluxes observed in the reoxygenation treatment.…”
Section: Table 2 Measured Sediment-to-water Release Fluxes Of Dissolmentioning
confidence: 99%
“…This was explained by coprecipitation of interstitial colloids and DOM and associated POPs when ferrous oxides precipitated following aeration. Pedersen et al (16) report a 24% decrease in pore water DOM when aerating estuarine sediments, attributable to DOM coagulation with precipitating Fe(OH)3. Baltic Sea sediments contain large amounts of organic matter and coprecipitation effects are plausible explanations to the stabilized or reduced contaminant fluxes observed in the reoxygenation treatment.…”
Section: Table 2 Measured Sediment-to-water Release Fluxes Of Dissolmentioning
confidence: 99%
“…The anoxic treatments typically had greater amounts of DOC than oxic. Increased DOC in anoxic treatment may be attributed to several factors; (i) greater solubility of organic matter at the higher pH level of the anoxic treatment and (ii) formation of ferric hydroxides as a co-precipitant of DOC in oxic soil samples [44,45]. As SOM is often considered to be the chief sorbent for hydrophobic compounds, it was therefore anticipated to dominate the sorption of PCP; however, subsequent dissolved organic matter (DOM) formation offset its impact in this study in agreement with previous reports [46,47].…”
Section: Characterization Of Original and Isolated Soilsmentioning
confidence: 99%
“…Pedersen et al [6] found that by exposing anoxic sediment pore water from three different estuarine sites to DO, partitioning of a tetra-CB between pore-water DOM and the freely dissolved phase decreased at two sites and did not change at the third. Lin et al [8] found changes in the diffusive flux of a tetra-CB from the sediment bed to the water column depended on changes in partitioning Fig.…”
Section: Large-scale Sediment Resuspensionsmentioning
confidence: 99%
“…The lack of significant change in PCB partitioning in the present study is probably due to lack of change in water column ionic strength (e.g., pH) despite differences in water column DO. Both Pedersen et al [6] and Lin et al [8] demonstrated the effects of oxic state were both ionic strength-and site-dependent, and indicated site-specific sorption coefficients are necessary for evaluating the effect of remediation activities.…”
Section: Large-scale Sediment Resuspensionsmentioning
confidence: 99%
See 1 more Smart Citation